The water quality and biological indicators of estuarine and marine waters affected by shrimp farming effluents in Bireuen Regency, Aceh - Izwar, Akmal; Fauza, Saniar; Muktitama, Asih Makarti; Nugrahawati, Anis; Azhar, Rossy; Putra, Dani Pratama; Hakim, Syahirman; Musarady, Yoga (Universitas Malikussaleh, 2025)
Intensive whiteleg shrimp farming has the potential to degrade water quality through the accumulation of organic matter and nutrients in coastal ecosystems. This study aimed to evaluate differences in water quality between estuarine and marine waters in Bireuen Regency, Aceh, and to associate them with plankton and bacteria as ecological indicators. The research was conducted from July to August 2025 at three estuarine and three marine stations, analyzing physical, chemical, and biological parameters. Results showed that estuarine waters had higher TSS (9–16 mg/L), NH₃ (0.80 mg/L), BOD (4.6–7.1 mg/L), and COD (32–33 mg/L) than marine waters, associated with the presence of Nitzschia spp., Ceratium hirundinella, Brachionus rotundiformis, Aeromonas hydrophila, and Vibrio parahaemolyticus. In marine waters, although DO and salinity were more stable, eutrophication indicators included Noctiluca spp., copepods (Acartia, Oithona), V. alginolyticus, and Photobacterium damselae. These findings indicate that estuaries act as pollution hotspots while marine waters are also affected, emphasizing the need for ecosystem-based management of shrimp aquaculture effluents. Keywords: Estuary; Marine Waters; Plankton; Vibrio spp; Water Quality; Whiteleg Shrimp